2013
DOI: 10.1371/journal.pone.0057381
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Massively Parallel Sequencing for Fetal Aneuploidy Detection from Maternal Plasma

Abstract: BackgroundCirculating cell-free (ccf) fetal DNA comprises 3–20% of all the cell-free DNA present in maternal plasma. Numerous research and clinical studies have described the analysis of ccf DNA using next generation sequencing for the detection of fetal aneuploidies with high sensitivity and specificity. We sought to extend the utility of this approach by assessing semi-automated library preparation, higher sample multiplexing during sequencing, and improved bioinformatic tools to enable a higher throughput, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 26 publications
4
117
0
Order By: Relevance
“…The cffDNA in maternal peripheral blood consists of small fragments that are unstable, and its concentration reduces at a constant speed after collecting blood because of the activity of DNases. It is difficult to extract cffDNA from maternal peripheral blood after 6 hours (Jensen et al, 2013;Wong et al, 2013). Thus, we isolated the cffDNA immediately after collecting the blood samples to avoid DNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The cffDNA in maternal peripheral blood consists of small fragments that are unstable, and its concentration reduces at a constant speed after collecting blood because of the activity of DNases. It is difficult to extract cffDNA from maternal peripheral blood after 6 hours (Jensen et al, 2013;Wong et al, 2013). Thus, we isolated the cffDNA immediately after collecting the blood samples to avoid DNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This focused treatment cannot be accomplished through genetic diagnosis of CAH by amniocentesis and chorionic villus sampling. It has been shown that detection of fetal chromosomal aneuploidy from cffDNA in the maternal plasma using MPS has a high sensitivity and specificity leading to its commercial use [31][32][33]. While our data are promising, the number of studied cases is still relatively small, requiring further validation in large-scale prospective studies.…”
mentioning
confidence: 84%
“…The most established methods have used MPS to detect certain autosomal trisomies, sex chromosome aneuploidies, and other copy number variations (CNVs) with high analytical sensitivity and specificity (1)(2)(3)(4)(5)(6). In addition, the utility of sequencing ccf DNA has been further demonstrated by detecting mutations associated with Mendelian traits and the reconstruction of the entire fetal genome (7)(8)(9)(10).…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%